System of organization and functioning of mechanisms for ensuring the operational safety of buildings - TYSLENKO, Oleksandr; BYKOV, Serhiy; KATIN, Oleksandr (Ways to Improve Construction Efficiency, 2025)
The system of organization and functioning of mechanisms for ensuring the operational safety of buildings is considered as an integrated multi-level structure that combines technical, analytical, informational, and managerial components. In modern conditions of urban development intensification and the increasing complexity of architectural and structural solutions, it is essential to shift from fragmented methods of technical inspection to comprehensive management of operational reliability. The foundation of this process lies in the creation of digital-analytical monitoring systems capable of continuous observation of structural conditions, risk identification, material degradation forecasting, and prevention of emergency situations. Operational safety of buildings is understood as the ability of a structure to maintain functionality, structural integrity, and user comfort throughout its entire life cycle. It encompasses technical stability, energy efficiency, resistance to external impacts, and adaptability to changes in the technogenic environment. The functioning of such a system is based on a multi-level architecture in which each level – from sensor monitoring to management decision-making – performs a specific function while remaining integrated into a unified information space. The system includes diagnostic, analytical, prognostic, managerial, and digital modules that together ensure a closed data processing cycle. Sensor units collect primary parameters of the technical condition, analytical modules perform their evaluation, prognostic modules model development scenarios, and managerial modules implement preventive measures. The interaction among these components determines the system’s efficiency in preventing technical failures. A key element of the concept is the notion of serviceability – a condition under which a building maintains its functionality without exceeding serviceability limit states (SLS). This concept is consistent with national and international standards, including EN 1990:2002 (Eurocode), ISO 13822:2010, and DBN V.1.2-14:2018. According to these documents, serviceability is evaluated not only by the strength and stability of structures but also by comfort, energy efficiency, vibration stability, and durability.